2019
DOI: 10.1103/physrevlett.123.225101
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Tensor Elements Breaking the Frozen-In Law During Reconnection in Earth’s Magnetotail

Abstract: Aided by fully kinetic simulations, spacecraft observations of magnetic reconnection in Earth's magnetotail are analyzed. The structure of the electron diffusion region is in quantitative agreement with the numerical model. Of special interest, the spacecraft data reveal how reconnection is mediated by off-diagonal stress in the electron pressure tensor breaking the frozen-in law of the electron fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 34 publications
9
51
0
Order By: Relevance
“…This result was first derived in (Le et al, 2010) and has been verified in numerical studies (Le et al, 2013, 2016; Ng et al, 2011) and spacecraft observations (Egedal et al, 2019). Equation is perhaps an unexpected result as this scaling law for B H implies that the current across the EDR is set by pressure anisotropy and not by the reconnection electric field as is expected from resistive reconnection models (Parker, 1957).…”
Section: The Firehose Parameter and Anisotropy Scalingsupporting
confidence: 71%
See 2 more Smart Citations
“…This result was first derived in (Le et al, 2010) and has been verified in numerical studies (Le et al, 2013, 2016; Ng et al, 2011) and spacecraft observations (Egedal et al, 2019). Equation is perhaps an unexpected result as this scaling law for B H implies that the current across the EDR is set by pressure anisotropy and not by the reconnection electric field as is expected from resistive reconnection models (Parker, 1957).…”
Section: The Firehose Parameter and Anisotropy Scalingsupporting
confidence: 71%
“…The regime of low guide magnetic field B g / B rec < 0.15 is particularly important to reconnection in the Earth magnetotail. For symmetric inflow conditions, kinetic simulation studies show that this low guide field regime can be further divided into a regime of no electron jets 0.05 < B g / B rec < 0.15 and a regime B g / B rec < 0.05 with the formation of moderate length 30 d e electron jets (Goldman et al, 2011; Hesse et al, 2008; Karimabadi et al, 2007; Le et al, 2010; Shay et al, 2007), directly relevant to observations in the Earth's magnetotail, (Egedal et al, 2019; Torbert et al, 2018). In this letter, we extend this physics understanding to account for asymmetries in the two inflow regions setting the upstream condition for the EDRs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[2018] and Figure 2 from Egedal et al. [2019]). J. Chen (1992) and Büchner and Zelenyi (1989) detailed quasiadiabatic particle dynamics, in which particles in fields with curvature scales comparable to their gyroradii behave in a mixture of structured gyromotion (adiabatic) and chaotic scattering (nonadiabatic) depending strongly on their gyrophase.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that magnetic tension resulting under a low reconnection rate (^A A of order 0.1 mV m ?6 ) ( Fig. 4b) was not strong enough to accelerate electrons, injected into the ECS at a high rate (equivalent to _`a,I = 1 − 2 mV m ?6 ) ( as well as other EDRs 4,9 , and earlier studies demonstrated that they can quantitatively account for the electric field ( I ) of fast reconnection as observed 16,17 . We derive a diffusion equation…”
mentioning
confidence: 77%